Total Quality Management as a Profitability Factor in the Hotel Industry - Milovanović, Vesna S (Industrija, 2014)
This paper focuses on assessing the impact of TQM implementation on the financial performance of hotels. According to the previous studies from Spain, Singapore, Malaysia, and the USA, an empirical investigation was conducted in Serbia during the first quarter of 2013. The findings revealed that the hotels practiced TQM at a relatively high level, especially customer orientation and teamwork. However, the analysis did not yield clear evidence that a higher level of TQM implementation impacted positively on the financial performances of hotels. The present research complements the existing literature on total quality management, and is the first attempt in Serbia to measure the financial consequences of TQM implementation. It aimed to raise the awareness among hoteliers regarding the importance of quality, and to support further analysis on the effects of TQM, especially in developing countries, which generally lack research of this kind, particularly in the hotel industry.
Keywords: Quality management; Hotel industry; Financial performance; Profitability